SRIKANDI LINTAS IMAN : Praktik Gerakan Perempuan dalam Menyuarakan Perdamaian di Yogyakarta - Wahyu, Retno; Perdanawati, Sari; Maulida, Nur (Jurnal Sosiologi Reflektif, 2019)
Based on the research conducted by Setara Institute in 2017 shows that Yogyakarta is one of the ten intolerant cities in Indonesia. But this reality is inversely proportional to tourism promotion about Yogyakarta which always considered as a tolerant city. Problems regarding intolerance appear as an arena of identity contestation and refer to certain interests. As a result, intolerance arises not only in the form of utterances but also acts of violence, one of the issues that arises is intolerance towards groups of different religions. Among the discourses on intolerance, there are various movements of society that attempts jointly to realize tolerant values in the society. One of them is a women’s movement that known as Srikandi Lintas Iman, namely women are from various faiths (Islam, Christianity, Catholicism, Hinduism, Buddhism and Confucianism) who take part in voicing peace issues among the diversity of life in Yogyakarta. This study aims to explain the dynamics of the movement and the efforts that made by Srikandi Lintas Iman in voicing peace issues. This research will be conducted by using qualitative method through a phenomenological approach. This research will interview members of Srikandi Lintas Iman consisting of women with various educational, occupational and religious backgrounds.